2003
DOI: 10.1128/aac.47.1.161-165.2003
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibilities to and Bactericidal Activities of Garenoxacin (BMS-284756) and Other Antimicrobial Agents against Human Mycoplasmas and Ureaplasmas

Abstract: The in vitro susceptibilities to garenoxacin (BMS-284756), an investigational des-fluoroquinolone, and eight other agents were determined for 63 Mycoplasma pneumoniae, 45 Mycoplasma hominis, 15 Mycoplasma fermentans, and 68 Ureaplasma sp. isolates. Garenoxacin was the most active quinolone, inhibiting all isolates at <1 g/ml. The garenoxacin MIC at which 90% of isolates are inhibited (MIC 90 s; <0.008 g/ml) was at least 4-fold less than those of moxifloxacin and clindamycin, 8-fold less than that of sparfloxac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 25 publications
6
64
2
1
Order By: Relevance
“…For M. hominis, others described a bactericidal activity of garenoxacin against one of two isolates (13) and a bactericidal activity of gatifloxacin against two of three isolates studied (14). In contrast to the results of Waites et al (13,14), we found some bactericidal activities for garenoxacin, gatifloxacin, and gemifloxacin against Ureaplasma spp.…”
contrasting
confidence: 56%
“…For M. hominis, others described a bactericidal activity of garenoxacin against one of two isolates (13) and a bactericidal activity of gatifloxacin against two of three isolates studied (14). In contrast to the results of Waites et al (13,14), we found some bactericidal activities for garenoxacin, gatifloxacin, and gemifloxacin against Ureaplasma spp.…”
contrasting
confidence: 56%
“…The MICs for LVX were two-to threefold lower than those of CIP; this has also been reported for Mycoplasma pneumoniae and Ureaplasma spp. (37). However the MIC of M2300 and M2321 for LVX was 4 mg/liter, and these two strains would be considered fluoroquinolone resistant.…”
Section: Discussionmentioning
confidence: 99%
“…The current taxonomic designations included in class Mollicutes comprise 4 orders, 5 families, 8 genera, and about 200 known species that have been detected in humans, vertebrate animals, arthropods, and plants. M. pneumoniae is a member of the family Mycoplasmataceae and order Mycoplasmatales (435).…”
Section: Mollicute Taxonomy and Classificationmentioning
confidence: 99%